2011
DOI: 10.1186/1475-2875-10-41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of IPTi on malaria using routine health information from sentinel health centres in southern Tanzania

Abstract: Background: Intermittent preventive treatment of malaria in infants (IPTi) consists of the administration of a treatment dose of sulphadoxine-pyrimethamine (SP) at the time of routine vaccinations. The use of routine Health Management and Information Services (HMIS) data to investigate the effect of IPTi on malaria, anaemia, and allcause attendance in children aged 2-11 months presenting to 11 health centres in southern Tanzania is described. Methods: Clinical diagnosis of malaria was confirmed with a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Programmatic changes such as adoption of RDTs at facilities, stock-outs, changes in RDT brand or antigen combination, introduction of systematic quality assurance and quality control approaches for monitoring RDT users, or even timing of refresher training for health workers on malaria case management are additional contextual factors which could be incorporated into impact evaluation. 67 …”
Section: Further Considerations For Impact Evaluation Design Using Hmmentioning
confidence: 99%
“…Programmatic changes such as adoption of RDTs at facilities, stock-outs, changes in RDT brand or antigen combination, introduction of systematic quality assurance and quality control approaches for monitoring RDT users, or even timing of refresher training for health workers on malaria case management are additional contextual factors which could be incorporated into impact evaluation. 67 …”
Section: Further Considerations For Impact Evaluation Design Using Hmmentioning
confidence: 99%
“…Our search retrieved only one study aiming to evaluate the PE of IPTi. It was a CCS conducted among infants in Tanzania and its main result was that the PE against occurrence of clinical malaria cases was 18% and not significant (95% CI -129–71% 165 ).…”
Section: Resultsmentioning
confidence: 99%
“…The last step in the model was that there should be some evidence of reduced malaria morbidity, which was indeed the case in the study [ 8 , 9 ]. Taking all these elements together, it seems likely that a combination of (i) lack of power combined with (ii) suboptimal coverage and (iii) increasing levels of drug resistance undermined this attempt to estimate the impact of IPTi on child survival.…”
Section: Discussionmentioning
confidence: 97%
“…The current study included household surveys in 2006 which suggested a modest impact of IPTi on malaria parasitaemia (from 38% to 31%, p = 0.06) and anaemia (from 88% to 80%, p = 0.02), despite coverage which was lower than anticipated [ 8 ]. Morbidity monitoring of malaria in 11 sentinel health facilities suggested that IPTi was associated with a reduction in clinical malaria of between 18% and 54%, depending on the scope of the analysis, although no differences reached statistical significance [ 9 ]. A recent pooled analysis of the efficacy of IPTi in six individually randomized studies in infants from Tanzania, Mozambique, Ghana and Gabon concluded that IPTi prevented 30% of clinical malaria episodes (95% CI 20-39) and 23% of all-cause hospital admissions (95%CI 10-34) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation